LIFETIME LAMB PRODUCTION OF NILAGIRI EWES - IYUE, M; KUMAR, R ANIL; VENKATARAMANAN, R; SREEKUMAR, C (The Indian Journal of Animal Reproduction, 2022)
The reproductive rate and lifetime productivity of ewes of Nilagiri sheep was assessed as a trait of ewe and expressed in terms of number of lambs produced (TLB), number of lambs weaned (TLW) and total weight weaned (TWW). Data from 2146 lambing records of Nilagiri ewes born during the period from 1978 to 2001 were analyzed. The mean number of lambs born per ewe during their lifetime varied from 3.69 ± 0.14 to 5.08 ± 0.36 for the different periods with an overall mean of 4.59 ± 0.12. The differences in total lambs born between the periods is significant (P<0.01). For the trait of TLW, the means for different periods varied form 2.65 ± 015 to 4.60 ± 015 and the overall mean was 3.42 ± 0.12. Higher weaning percentage were recorded in earlier years than in recent years of the study period and the differences in weaning percentage between periods was significant (P<0.01). The total weight weaned (TWW) ranged from 26.77 ± 1.50 to 45.95 ± 3.67 kg. The overall mean for this trait was 32.86 ± 1.19 kg. The heritability estimate for the reproductive traits were 0.377 ± 0.201(TLB), 0.505 ± 0.215 (TLW) and 0.537 ± 0.218 (TWW)